2020
DOI: 10.1016/j.jiph.2020.09.023
|View full text |Cite
|
Sign up to set email alerts
|

Comparative epidemiology between the 2009 H1N1 influenza and COVID-19 pandemics

Abstract: In a short time, humanity has experienced two pandemics: the influenza A virus pandemic (pH1N1) in 2009 and the coronavirus disease 2019 (COVID-19) pandemic in 2020. Therefore, it is likely that the general population will erroneously seek to compare the two pandemics and adopt similar attitudes in facing them. However, the two pandemics have their intrinsic characteristics that distinguish them considerably; for example, the virulence of the infectious agents and the availability of treatment and vaccine. Con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
60
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(65 citation statements)
references
References 77 publications
1
60
0
4
Order By: Relevance
“…However, many perceived the H1N1 pandemic to be a relatively mild disease, which may have played a role in the subsequent support of vaccine donation [15]. While the ultimate morbidity and mortality of COVID-19 will not be known for some time, it is clearly a more severe disease than H1N1 [7,9], which may affect countries' as well as their citizens' willingness to donate a future vaccine. In addition, Kumar et al [15] found that party affiliation, U.S. nativity, and income were all significantly related to views of the amount of H1N1 vaccine to be donated with Democrats more likely to support donation than Republicans, immigrants more likely to support vaccine donation than those who were native born, and those who had a lower income more likely to support higher levels of donation than those with higher incomes.…”
Section: Introductionmentioning
confidence: 99%
“…However, many perceived the H1N1 pandemic to be a relatively mild disease, which may have played a role in the subsequent support of vaccine donation [15]. While the ultimate morbidity and mortality of COVID-19 will not be known for some time, it is clearly a more severe disease than H1N1 [7,9], which may affect countries' as well as their citizens' willingness to donate a future vaccine. In addition, Kumar et al [15] found that party affiliation, U.S. nativity, and income were all significantly related to views of the amount of H1N1 vaccine to be donated with Democrats more likely to support donation than Republicans, immigrants more likely to support vaccine donation than those who were native born, and those who had a lower income more likely to support higher levels of donation than those with higher incomes.…”
Section: Introductionmentioning
confidence: 99%
“…This raised the suspicion of possible H1N1 infection among the SARI patients. The influenza viruses and SARS-CoV-2 are both efficient in causing respiratory disease because they easily spread among humans through oral and nasal droplets 1 . In patients with COVID-19, blood tests typically show leukopenia and lymphopenia and most chest computed tomography scans show ground-glass opacity and consolidation with bilateral lung involvement.…”
Section: Resultsmentioning
confidence: 99%
“…pneumonia as coronavirus disease 2019 (COVID-19), whereas the International Committee on Taxonomy of Viruses has named it severe acute respiratory syndrome corona virus 2 (SARS-CoV-2) 15 . Approximately a decade ago, the World Health Organization (WHO) declared the first of two global epidemics: on June 11, 2009, an influenza A H1N1 pandemic (pH1N1); the second and current pandemic of corona virus disease 2019 (COVID-19) was declared on March 11, 2020. The two pandemics of the 21st century originated from different viruses, but they have some similarities, such as they were both caused by enveloped RNA viruses, usually of spherical morphology 1 . Other points that call attention are related to the frequent mutations and diversity of the hosts that can be infected 1 .Infections of the respiratory system, such as influenza-like illness, cold, bronchitis and pneumonia are the main causes of morbidity and mortality worldwide.…”
mentioning
confidence: 99%
See 2 more Smart Citations